Serum NGAL, cystatin C and urinary NAG measurements for early diagnosis of contrast-induced nephropathy in children - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2016)
Aim: The study investigated a number of biomarkers for the early diagnosis of contrast-induced nephropathy (CIN), which is an important cause of acute kidney injury (AKI). Material and methods: The study included 91 children scheduled for elective cardiac angiography and 50 healthy controls. Biomarkers including serum (s) and urinary (u) sodium, serum and u-creatinine, s-cystatin-C, serum neutrophil gelatinase-associated lipocalin (NGAL) and urinary N-acetyl beta glucosaminidase (u-NAG)/creatinine ratio were measured 4 times sequentially in the patients and once in the controls. Results: The patient group comprised 40 males (44%) and 51 females (56%) while the control group comprised 16 males (32%) and 34 females (68%). Age, gender, s-creatinine, estimated-glomerular filtration rate (eGFR), s-cystatin-C and fractional-excretion of sodium did not differ significantly between the groups. Serum sodium and s-NGAL were found to be lower in the patients than those of in the controls, while their u-NAG/creatinine ratio was found to be higher. Sequential data analysis revealed that s-NGAL and u-NAG/creatinine ratio increased in the first 6h after radiocontrast media (RCM) administration and decreased at 12 and 24h. Serum BUN and s-cystatin-C levels also showed a significant difference during the 24-h follow-up. eGFR, s-sodium and s-creatinine levels did not change in the following period. Serum cystatin-C levels revealed a significant negative correlation with eGFR. Administered RCM doses showed a positive correlation only with u-NAG/creatinine ratios. Conclusion: In the first 24h, s-cystatin-C, s-NGAL and especially u-NAG/creatinine ratio showed promise as biomarkers, but eGFR is not adequate for early diagnosis of CIN. Sequential measurement of biomarkers may contribute to more accurate diagnosis of AKI.
Keywords: Acute kidney injury; contrast-induced nephropathy; cystatin C; N-acetyl beta glucosaminidase; neutrophil gelatinase-associated lipocalin; ACUTE KIDNEY INJURY; GELATINASE-ASSOCIATED LIPOCALIN; ACETYL-BETA-GLUCOSAMINIDASE; EARLY PREDICTIVE BIOMARKER; EXCRETION; DISEASE